2022
DOI: 10.3390/foods11040621
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step PEF Processing for Enhancing the Polyphenol Concentration and Decontaminating a Red Grape Juice

Abstract: This study’s aim is to evaluate Pulsed Electric Fields (PEF) technology as an alternative method for the processing of red grape juice. For this purpose, two PEF treatments were applied: first to grapes for polyphenol enrichment of the juice, and subsequently for microbial decontamination of the obtained juice. Juice obtained from PEF‑treated grapes (5 kV/cm, 63.4 kJ/kg) had the polyphenol content 1.5-fold higher and colour intensity two times higher of control juices by spectrophotometric measurement (p ≤ 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…Therefore, it is possible to enhance the release of thermally unstable bioactive compounds under mild processing conditions by optimizing electric field strength in combination with an appropriate solvent system. Delso et al [95] assessed the viability of PEF technology as a potential alternative approach for the processing of red grape juice, so they studied the enhancement of juice derived from grapes. The sample was treated with PEF (electric field strength at 5 kV/cm, specific energy at 63.4 kJ/kg, and pulse width 40 µs) and had a TPC 1.5 times higher than that of untreated grapes, 1434.30 mg GAE/L and 916.10 mg GAE/L, respectively.…”
Section: Grapesmentioning
confidence: 99%
“…Therefore, it is possible to enhance the release of thermally unstable bioactive compounds under mild processing conditions by optimizing electric field strength in combination with an appropriate solvent system. Delso et al [95] assessed the viability of PEF technology as a potential alternative approach for the processing of red grape juice, so they studied the enhancement of juice derived from grapes. The sample was treated with PEF (electric field strength at 5 kV/cm, specific energy at 63.4 kJ/kg, and pulse width 40 µs) and had a TPC 1.5 times higher than that of untreated grapes, 1434.30 mg GAE/L and 916.10 mg GAE/L, respectively.…”
Section: Grapesmentioning
confidence: 99%
“…The pulsed electric field (PEF) has gained popularity as it is one of the most appropriate non-thermal processing technologies to process liquid foods with low viscosity. Although studies mostly reported on different types of food, including fruit and vegetable juices Kantala et al, 2021;Delso et al, 2022;Evrendilek, 2022;Oziembłowski et al, 2022;Roobab et al, 2022), a limited number of studies are reported with LRS processing by PEF. Processing of Mentha piperita essential oil-added LRS by PEF provided a shelf-life extension of 6 weeks (Demir et al, 2022).…”
Section: Introductionmentioning
confidence: 99%